2009
DOI: 10.2500/ajra.2009.23.3373
|View full text |Cite
|
Sign up to set email alerts
|

Canine Fossa Trephine for the Severely Diseased Maxillary Sinus

Abstract: CFT allows for complete clearance of all gross disease in the maxillary sinus. CFT decreases the chance of disease recurrence in patients with severe NP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 15 publications
0
36
0
2
Order By: Relevance
“…However, this dogma was recently contested with the report of improved outcomes with aggressive surgical management of the mucosa. 8 Kupferberg's et al's 13 original work showed recurrence in 11 of 12 AFS patients by 14.5 months when not maintained on oral steroids, whereas Seiberling et al's 8 more aggressive partial thickness mucosa removal through a CFT led to only 9 of 19 AFS recurrences without the need for long-term oral glucocorticoids.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, this dogma was recently contested with the report of improved outcomes with aggressive surgical management of the mucosa. 8 Kupferberg's et al's 13 original work showed recurrence in 11 of 12 AFS patients by 14.5 months when not maintained on oral steroids, whereas Seiberling et al's 8 more aggressive partial thickness mucosa removal through a CFT led to only 9 of 19 AFS recurrences without the need for long-term oral glucocorticoids.…”
Section: Discussionmentioning
confidence: 94%
“…[1][2][3][4][5][6] However, other pathologies, including allergic fungal sinusitis and tumors, may require extensive exposure and more thorough mucosal treatment. [6][7][8] It is therefore reasonable for surgeons to have at their disposal a number of well-studied approaches to maxillary pathology. The canine fossa trephination (CFT) technique was developed based on historical experience with the Caldwell Luc approach to create a direct route through the anterior face of the maxilla while minimizing postoperative morbidity.…”
mentioning
confidence: 99%
“…Other evidence demonstrates the utility of canine fossa trephine/puncture in recalcitrant disease [3,4 & ,14]. Sieberling et al [14] demonstrated that in 67 patients with an average of 2.83 previous endoscopic sinus surgeries, the Caldwell-Luc trephine procedure resulted in clearance of disease. This is contrary to evidence by Lee et al [13] that showed no difference in outcomes in a randomized control trial comparing Caldwell-Luc procedure and endoscopic maxillary antrostomy.…”
Section: Key Pointsmentioning
confidence: 97%
“…This is especially true when considering the alternative approaches mentioned, such as the canine fossa approach, mega-antrostomy, or medial maxillectomy [13, 14]. In view of the unfavorable angle for reaching the inaccessible areas of the sinus using the MMA approach, an endoscopic canine fossa approach to the maxillary sinus in severe disease and nasal polyposis has been recently described in detail [15, 16]. However, to avoid the known disadvantages of the transcanine approach (facial swelling, facial numbness, teeth/gum numbness, and the need for surgical assistance), we prefer to use the routine transnasal endoscopic approach to reach these remote areas.…”
Section: Discussionmentioning
confidence: 99%